Innovation in Acid-Base Learning (PasamBa) through Ecoprint Batik as a Contextual Strategy to Improve Understanding of Fashion Design Students in SMK - Meriza Faradilla; Miswatul Hasanah (Postgraduate, University of Mataram, 2026)
This study aims to test the effectiveness of PAsamBa (Acid-Base Learning) learning innovation integrated with ecoprint batik practice in improving conceptual understanding and vocational skills of eleventh-grade students in the Fashion Design expertise program at Vocational High Schools (SMK). The acid-base concept has direct relevance to textile skill processes such as mordanting, color fixation, and pH stability of natural dyes, which are important in sustainable fabric dyeing. The study used a one-group pretest-posttest design involving 73 students from three vocational high schools in Aceh. The instruments included a 20-item acid-base concept understanding test (α = 0.86) and a vocational skills rubric that assessed procedural accuracy, color stability, and ecoprint pattern quality. The results showed a significant increase (t( 72) = 12.86; p < 0.001), with the average score increasing from 43.69 to 80.53 and an N-gain value of 0.67 (medium-high category, approaching high). Students' vocational skills also improved, with an average process score of 3.49 and a product score of 3.41 (scale 4). These results demonstrate that the PAsamBa–Ecoprint approach effectively integrates chemistry learning with contextual textile practices to strengthen students' conceptual understanding and readiness for the creative fashion industry.